Effects on staff outcomes and process evaluation of the educating nursing staff effectively (TENSE) program for managing challenging behavior in nursing home residents with dementia: A cluster-randomized controlled trial. (August 2021) - Bielderman, Annemiek; Nieuwenhuis, Aniek; Hazelhof, Theo J.G.M.; van Gaal, Betsie G.I.; Schoonhoven, Lisette; Akkermans, Reinier P.; Spijker, Anouk; Koopmans, Raymond T.C.M.; Gerritsen, Debby L.
Abstract: Background: Challenging behavior is prevalent in people with dementia residing in nursing homes and places a high burden on the nursing staff of dementia special care units. This study evaluates an educational program for nursing staff for managing challenging behavior: The Educating Nursing Staff Effectively (TENSE) program. This program can be tailored to care organizations' wishes and needs and combines various learning styles. Objective: The aim of this cluster-randomized controlled trial was to examine the short-term (3 months) and long-term (9 months) effects of the TENSE training program on experienced stress, work contentment, and stress reactions at work in nursing staff working in dementia special care units. Design: Cluster-randomized controlled trial. Methods: Nursing staff members of 18 dementia special care units within nine nursing homes from different Netherlands regions were randomized into an intervention (n = 168) or control (n = 129) group. The TENSE program consisted of a three-day training course and two follow-up sessions after three and six months, respectively. The primary outcome was stress experienced by nursing staff measured with the Utrecht Burnout Scale - C . Secondary outcomes were work contentment and stress reactions at work. Furthermore, process evaluation data on the reach of and compliance with the program and the program's feasibility and relevance were collected. Data were collected between November 2012 and November 2014. Results: In general, the participants appreciated the quality and relevance of the TENSE training and evaluated the content of the training as beneficial. The TENSE training had no effect on the components of experienced stress, i.e., emotional exhaustion (p = 0.751), depersonalization (p = 0.701), and personal accomplishment (p = 0.182). Furthermore, no statistically significant effects of the intervention on work contentment and stress reactions at work were found. Conclusions: The TENSE training program did not have an effect on experienced stress, work contentment, nor stress reactions at work of nursing staff working in dementia special care units . In future studies, more focus on practicing new skills seems needed. Trial registration: NTR (Dutch Trial Registration) number NTR3620